Cultural Disintegration and Colonial Intrusion in Chinua Achebe’s Things Fall Apart: A Critical Analysis of Igbo Society - ., P. Praseeba; Royappa, R. C. Sheila (Journal of Ecohumanism, 2024)
Chinua Achebe’s Things Fall Apart provides an in-depth exploration of Igbo society, its customs, and the devastating effects of European colonization. This paper examines the foundational beliefs of the Igbo people, including their socio-political structures, religious practices, gender roles, and agricultural dependence, which shaped their identity and way of life. The arrival of Christian missionaries and colonial administrators disrupted these traditions, creating conflicts between generations, families, and societal structures. The introduction of Western education, legal systems, and monotheistic beliefs challenged the Igbo worldview, leading to a gradual cultural disintegration. Through an analysis of key events, symbolic elements, and character transformations in the novel, this study highlights the internal and external forces that contributed to the collapse of Igbo society. Additionally, a comparative perspective with Joseph Conrad’s Heart of Darkness is presented to contrast Achebe’s authentic depiction of African identity with Western portrayals of imperialism. By examining both historical and literary perspectives, this paper underscores the broader implications of colonialism on indigenous societies, emphasizing the loss of cultural heritage, identity, and autonomy.